A proposal of data – driven method for determining the weights of composite indicators - Kądziołka, Kinga (Propozycja metody wyznaczania wag składowych mierników taksonomicznych, 2021)
The paper proposed a simulation method for determining the weights of components of taxonomic measures. The method takes into account the degree of similarity of the final ranking to other rankings and other properties, e.g. the clustering ability of the measure. The analyses were performed on publicly available data published by the General Statistic Office, concerning selected characteristics of the labour market in Poland at the level of subregions. The results obtained by the proposed method depend on the initial set of weights vectors. Due to the fact that the proposed method does not provide an invariant solution for a given data set, the stability of the rankings obtained using this method was assessed. There was high consistency in the orderings of objects obtained in the consecutive repetitions of the procedure
Econometrics = Ekonometria, 2021, Vol. 25, No. 1, s. 49-62
Keywords: taxonomic measure; composite indicators; weighting schema; semi-standard deviation; labour market; Spearman’s corelation coefficient; miernik taksonomiczny; wagi zmiennych diagnostycznych; semi-odchylenie standardowe; współczynnik korelacji Spearmana; rynek pracy